An Investigation of Low Cost and Effective Tar Removal Techniques by Venturi Scrubber Producing Syngas Microbubbles and Absorbent Regeneration for Biomass Gasification. (May 2017) - Unyaphan, Siriwat; Tarnpradab, Thanyawan; Takahashi, Fumitake; Yoshikawa, Kunio
Abstract: The major challenge of biomass gasification technologies is the control of the tar concentration to acceptable level for each downstream application in order to prevent clogging and fouling problems. Low cost and high efficiency tar removal by combining a venturi scrubber and absorbent regeneration was proposed in order to enhance and maintain the tar removal performance in the long run. In this study, 2L of canola oil in a venturi scrubber and a regenerative unit was utilized in the lab-scale test. The results showed that the syngas microbubbles produced by the venturi scrubber enabled to increase the tar removal efficiency by 18% compared to the bubbling scrubber, while the tar removal efficiency could be maintained between 90% and 96% along 10 hours experiment by absorbent regeneration. Moreover, every time the canola oil was regenerated, the tar removal performance was recovered to more than 90% which is almost the same as the fresh canola oil performed.